FIRST MIDDLE DEVONIAN BIVALVES FROM ARGENTINA, NEW RECORDS FROM THE PUNTA NEGRA FORMATION AND INSIGHTS ON MIDDLE PALEOZOIC FAUNAS FROM THE PRECORDILLERA BASIN (Ameghiniana, 2015)
Middle Devonian bivalves from Argentina are reported for the first time, based on records of the Precordilleran Punta Negra Formation (Emsian–Frasnian?), San Juan Province. This finding is the youngest Devonian record of bivalves from southernmost South America. The impoverished bivalve association in the Punta Negra Formation includes five shallow infaunal deposit feeders, i.e. Nuculites argentinum Sánchez, Anthracoleda (Pseudoleda) minuta Sánchez, Praenucula sp., Deceptrix sp. and Praectenodonta sp. The distribution of the Silurian–Devonian bivalves from Precordillera shows a decreasing diversity trend during this interval, due to potential biases in sampling and paleoecology and thus suggesting that this trend might be apparent. Early and Middle Devonian bivalves from Precordillera show a strong cosmopolitan paleobiogeographic signature, in contrast with other geographically related basins showing endemic (Malvinokaffric Realm) signals during the Devonian. Contrarily, an endemic composition is recorded in the Precordillera Basin when based on coeval Malvinokaffric groups such as ostracods and trilobites. Although more information is needed, the cosmopolitan character of Devonian bivalve assemblages from the Argentine Precordillera Basin might be interpreted under the light of a unique history driving biogeographic processes affecting different taxonomic groups in different ways.Resumen. PRIMEROS BIVALVOS DEL DEVÓNICO MEDIO DE ARGENTINA, NUEVOS REGISTROS DE LA FORMACIÓN PUNTA NEGRA Y APRECIACIONES SOBRE LAS FAUNAS DEL PALEOZOICO MEDIO DE LA CUENCA DE PRECORDILLERA. Se dan a conocer los primeros registros de bivalvos del Devónico Medio (Emsiano–Frasniano?) de Argentina en la Formación Punta Negra, Precordillera de San Juan. Se identificó una asociación empobrecida integrada por cinco bivalvos infaunales detritívoros: Nuculites argentinum Sánchez, Anthracoleda (Pseudoleda) minuta Sánchez, Praenucula sp., Deceptrix sp. y Praectenodonta sp. La distribución de los géneros de bivalvos en el Silúrico-Devónico de la Precordillera, muestra una diversidad decreciente en este intervalo de tiempo. Sin embargo, esta tendencia podría ser aparente debido a posibles sesgos paleoeocológicos o derivados del muestreo en las asociaciones. Los bivalvos del Devónico Temprano y Medio de la cuenca de Precordillera son fuertemente cosmopolitas, en contraposición con los registros de endemismos (malvinocáfricos) de cuencas coetáneas geográficamente relacionadas. Además, es reconocible una signatura paleobiogeográfica endémica en otros grupos de esta cuenca como ostrácodos y trilobites. Si bien se necesita más información, es posible interpretar que el carácter cosmopolita de los bivalvos de la Precordillera Argentina respondería a una historia única de procesos biogeográficos que afectan de manera diferente a cada grupo taxonómico.